Putative analgesic activity of repeated oral doses of vitamin E in the treatment of rheumatoid arthritis. Results of a prospective placebo controlled double blind trial. Issue 11 (1st November 1997) - Edmonds, S E; Winyard, P G; Guo, R; Kidd, B; Merry, P; Langrish-Smith, A; Hansen, C; Ramm, S; Blake, D R
Abstract : OBJECTIVE: Vitamin E, the most potent naturally occurring lipid soluble antioxidant has been suggested to possess both anti-inflammatory and analgesic activity in humans. This double blind and randomised study used a broad spectrum of clinical and laboratory parameters to investigate whether there was any additional anti-inflammatory or analgesic effects, or both, of orally administered α-tocopherol in rheumatoid arthritis patients who were already receiving anti-rheumatic drugs. METHODS: Forty two patients were enrolled and treated with α-tocopherol (n=20) at a dose of 600 mg twice a day (2 × 2 capsules) or with placebo (n=22) for 12 weeks. The following parameters were measured: (1) Three clinical indices of inflammation—the Ritchie articular index, the duration of morning stiffness, and the number of swollen joints; (2) three measures of pain—pain in the morning, pain in the evening, and pain after chosen activity; (3) haematological and biochemical measures of inflammatory activity; (4) assays for the oxidative modification of proteins and lipids. RESULTS: All laboratory measures of inflammatory activity and oxidative modification were unchanged. Furthermore, the clinical indices of inflammation were not influenced by the treatment. However, the pain parameters were significantly decreased after vitamin E treatment when compared with placebo. CONCLUSION: The results provide preliminary evidence that vitamin E may exert a small but significant analgesic activity independent of a peripheral anti-inflammatory effect, but which complements standard anti-inflammatory treatment.